An Essential Collation to Study Horacio Castellanos Moya’s Insensatez - Dávila, Jesús (2023)
The hypothesis developed by this paper is that the document corrected and quoted by the narrator of Insensatez is not a faithful copy of the report Guatemala: Nunca más. The first reception of the novel in Spain is reconstructed, as the origins of a reading bias that tends to identify and confuse the historical document with that of fiction are traced; likewise, biographical data of Castellanos Moya relevant to the reading of Insensatez are analyzed. Finally, the most important critical contributions on the subject are discussed and two specific collations are presented to argue the central hypothesis of this work.